1990
DOI: 10.1002/aja.1001870406
|View full text |Cite
|
Sign up to set email alerts
|

Development and innervation of the abdominal muscle in embryonic Xenopus laevis

Abstract: The morphogenesis and innervation of the ventral abdominal musculature in Xenopus embryos was examined using microscopic techniques. Muscle development begins at Nieuwkoop and Faber Stage 31, when aggregates of undifferentiated cells form on the ventrolateral margins of rostral trunk myotomes. During subsequent stages, aggregates form and detach from progressively more caudal myotomes to form a series of seven discrete cell clusters (anlagen). The anlagen migrate ventrally in a cell-free space between the epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…The present lineage tracing study with a-cardiac actin cDNA probe and anti-sarcomeric actin monoclonal antibody confirmed the previous report (Lynch, 1990) that cells of abdominal muscle originated from the myotomes of dorsal mesoderm and clearly showed the migration pattern of abdominal muscle anlagen (Figs. 2 and 3).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present lineage tracing study with a-cardiac actin cDNA probe and anti-sarcomeric actin monoclonal antibody confirmed the previous report (Lynch, 1990) that cells of abdominal muscle originated from the myotomes of dorsal mesoderm and clearly showed the migration pattern of abdominal muscle anlagen (Figs. 2 and 3).…”
Section: Discussionsupporting
confidence: 91%
“…However, the mechanism of abdominal muscle migration to form ventral trunk musculature has been unrevealed until electron microscopic observations showing the general migration pattern of abdominal muscle in Xenopus laevis (Lynch, 1990). Genetic and molecular approaches to understand muscle development revealed a number of myoD family genes, the regulation mechanisms of gene expression, and morphological changes of muscle cells during differentiation.…”
mentioning
confidence: 99%
“…However, these tadpoles do contain hypaxial muscles, which form the rectus abdominus muscles (Lynch, 1990;Martin and Harland, 2001;Ryke, 1953). These are homologous to the inter-limb body wall muscles of amniotes (McDiarmid and Altig, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…3J.) This cell mass was abdominal muscle anlagen (precursor tissue of abdominal muscle), which migrates ventrally, expands, and differentiates into muscle (Lynch 1990). XRACK1 expression was also present in presumptive premigratory abdominal muscle cells and this continued during subsequent stages.…”
mentioning
confidence: 99%